The University of Kentucky : a pictorial history - Cone, Carl B. (University Press of Kentucky, 1989)
When the University of Kentucky was begun in 1865, it was merely an adjunct of a denominational college in Lexington. From that humble beginning has come a proud institution with an enrollment of 56,000 and with students, faculty, and facilities spread across a landscape extending to the boundaries of the Commonwealth. The University's graduates now include Nobel laureates, statesmen, and thousands of productive citizens whose influence reaches to the far corners of the world. In words and pictures, this book tells the story of the University's beginnings, its struggles for adequate funding, it.